Students use coconut shells to assist needy - Daily Express, (KK) (Daily Express (kk), 2017)
KUALA LUMPUR: Heaps of discarded coconut shells caught the attention of a group of Universiti Utara Malaysia (UUM) students in Kedah, prompting them to take the initiative to recycle the 'worthless' garbage as charcoal.